If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(R + -7) = -162 Reorder the terms: 6(-7 + R) = -162 (-7 * 6 + R * 6) = -162 (-42 + 6R) = -162 Solving -42 + 6R = -162 Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 6R = -162 + 42 Combine like terms: -42 + 42 = 0 0 + 6R = -162 + 42 6R = -162 + 42 Combine like terms: -162 + 42 = -120 6R = -120 Divide each side by '6'. R = -20 Simplifying R = -20
| -x-4=4x+6 | | -3-11=6y+16 | | 7x+8x-6= | | 5-8(7-n)=-91 | | 4+(-12)+23+(-8)= | | 136+38x=x+163 | | 2x-138=-7x+114 | | 15u-17u-(-20)=-6 | | 9x(-4)+3y-x+y-(-2)= | | 3x+1+6x=-89 | | 38x+136=x+163 | | 6x+5-5x=10 | | 5t=3(7t) | | -10-2x=6x+2(-7x+7) | | -8+7x+3x=-8 | | x+5-2x= | | Y=100-4n | | -7r+6t-8s-5r+12s+4t-t+2s-11r= | | 3c-3=6 | | -25=a(x-3)+3 | | 12-4x=3x^3-x^2 | | 8x-9x^3+1=0 | | .005x-.07=.02x+.0032 | | 18x^2+21x-49=0 | | 5=2+3s | | 5n+17=8(-8-3n)-6 | | 9-0.1k=9 | | 2-5v=-v+2(1+7v) | | x+5+2x= | | 12-7n=6-8n | | 3(2x+3)=2x+21 | | 59x-(21x+34)=0 |